2012
DOI: 10.1186/2228-5326-2-14
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured copper oxide-cotton fibers: synthesis, characterization, and applications

Abstract: Copper oxide nanoparticles were prepared and subsequently deposited onto surface of the cotton fibers by ultrasonic irradiation. The structure and morphology of the coated and un-coated cottons were examined by X-ray diffraction and scanning electron microscopy/energy dispersive X-ray analysis. These methods revealed that of CuO nanoparticles are crystalline and corresponds to monoclinic phase, and that these nanoparticles are physically adsorbed onto the cotton fiber surface. They have an average crystallite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 16 publications
1
51
0
Order By: Relevance
“…[9][10][11][12] Moreover, CuO nanomaterials mixed with various types of fabrics have also been previously reported to have significant antibacterial activity. [13][14][15] These nanomaterials based fabrics have been proposed to be used for application in medical garments. 14,15 It has been reported that physio-chemical behavior of CuO nanomaterials can be tailored via doping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Moreover, CuO nanomaterials mixed with various types of fabrics have also been previously reported to have significant antibacterial activity. [13][14][15] These nanomaterials based fabrics have been proposed to be used for application in medical garments. 14,15 It has been reported that physio-chemical behavior of CuO nanomaterials can be tailored via doping.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] These nanomaterials based fabrics have been proposed to be used for application in medical garments. 14,15 It has been reported that physio-chemical behavior of CuO nanomaterials can be tailored via doping. 16 Recently, various dopants have been used for achieving enhanced 18 There are very few reports on the bactericidal potency of Zn doped CuO nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Both were inoculated with E. coli and S. aureus in order to compare the antimicrobial effect of the two coating systems in a Gram negative and Gram positive model, respectively. The results showed that the sample with CuO NPs presented higher antibacterial activity than the sample coated with CuS nanoparticles which showed no reduction in the viability of tested bacteria [50]. Devi et al studied the antimicrobial activity of bulk, as-prepared and annealed CuO NPs against E. coli , Proteus mirabilis , Klebsiella spp., and their effect was comparable with the antimicrobial activity of gentamycin on these strains [9,51].…”
Section: Medical Applicationsmentioning
confidence: 99%
“…The assessment of water quality in surface water sources and drinking water using physical and chemical analysis does not provide complete information on the complex impact of pollutants on aquatic ecosystems. Therefore, the use of biological methods to determine the toxicity of these waters is particularly relevant [1,2]. Moreover, the toxicity of drinking water surface waters should be evaluated not only for humans, but also for fish populations and other aquatic organisms [3][4][5][6][7][8], especially for those who are actively involved in the processes of water quality formation.…”
mentioning
confidence: 99%